Poland Catching-Up Regions : Strengthening the Implementation of Work-Based Learning - World Bank Group (World Bank, Washington, DC, 2018)
Worldwide, Vocational Education and Training (VET) is receiving increasing attention, particularly as a potentially useful instrument to address high unemployment rates among youth. In 2016, the World Bank started providing technical assistance to the self government of Poland’s Świętokrzyskie region, aimed at strengthening the implementation of Work-Based Learning (WBL) in technical schools. Through Work-Based Learning (WBL), students develop essential skills by participating in activities on enterprise premises, including onsite training and particularly contributing to business operations. This support was part of a formal program of collaboration between the government of Poland, two regional self governments, the European Commission (EC), and the World Bank, with the aim to improve the impact of European Union (EU) financing allocated to improve innovation, employment, and economic growth in catching-up regions in Poland. As part of this programme, the World Bank provided technical assistance to the regional governments on a number of priority areas as proposed by the regions. In the Świętokrzyskie region, the regional government selected the strengthening of the implementation of WBL in VET as one of the priority areas. This report summarizes the main activities, findings, and outcomes of the collaboration to strengthen WBL in VET in Świętokrzyskie.